2007
DOI: 10.1007/s10350-007-9072-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Invasion to Auerbach's Plexus is an Important Prognostic Factor in Patients with pT3-pT4 Colorectal Cancer

Abstract: Perineural invasion defined as cancer invasion to Auerbach's plexus is an important prognostic factor for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 25 publications
4
40
2
3
Order By: Relevance
“…In contrast to our results, other studies previously confirmed NI as a prognostic factor in colon cancer (28). However, most of these studies have quite low sample size, limited to certain tumor stages and do not distinguish between rectal and colon cancer, which represent biologically different cancer entities (27)(28)(29)(30).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, other studies previously confirmed NI as a prognostic factor in colon cancer (28). However, most of these studies have quite low sample size, limited to certain tumor stages and do not distinguish between rectal and colon cancer, which represent biologically different cancer entities (27)(28)(29)(30).…”
Section: Discussioncontrasting
confidence: 99%
“…A major difference from other definitions of NI in colon cancer is the inclusion of invasion of Auerbach's plexus to the possible manifestations of NI in our study. Interestingly, there is only 1 study in literature that defined perineural invasion in colon cancer as invasion only into the AuP with a prevalence of 24% (27). The invasion of peripheral nerves was neither mentioned nor examined in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported on both intra and extramural perineural invasion [13,14,42]. Fujita [13] defined perineural invasion as cancer invasion to the Auerbach plexus and reported perineural invasion to be a more important prognostic factor than venous and lymphatic invasion in patients with colorectal cancer.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Fujita [13] defined perineural invasion as cancer invasion to the Auerbach plexus and reported perineural invasion to be a more important prognostic factor than venous and lymphatic invasion in patients with colorectal cancer. Ueno et al, 2013 [14], defined intramural perineural invasion as cancer spread along the Auerbach plexus and extramural perineural invasion as the histological finding of tumour cells invading or spreading along nerve fascicles external to the muscularis propria.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…7 The prognostic significance of PNI is widely advocated in malignancies of the head and neck and prostate, [8][9][10] but controversies exist in colorectal cancer. [11][12][13][14] In T1-2 early rectal cancer, PNI is one of the adverse pathologic features in selecting patients undergoing local excision. But whether it can be used as a criterion to select patients receiving chemoradiotherapy in T3N0 patients is still unknown to us.…”
mentioning
confidence: 99%